A study of quantitative and qualitative analysis of standardized speech samples in persons suffering from dysarthria due to various neurological disorder - Maheshwari, Somesh (International Journal of Advances in Medicine, 2020)
Background: Dysarthria is manifested as a disorder of movement, it is important to recognize that sensori-motor integration (with tactile, proprioceptive, and auditory feed-back representing the crucial sensory components) is essential to speech motor control, from this standpoint, most or all dysarthria localized to the central nervous system should be thought of as sensori-motor rather than simply motor disturbances. Methods: This non-interventional, cross-sectional comparative, observational study, conducted in 100 study subjects (50 cases and 50 controls) from March 2016 to February 2017 at MGM medical college and MY hospital Indore, MP, India. Results: The mean age of normal population was 53 years and that of dysarthric population was 55 years. Among the dysarthric group, there were 10 cases of ataxic dysarthria, 23 cases of spastic dysarthria, and 9 cases of hypo kinetic dysarthria. There were 20 cases of mild dysarthria 19 cases of moderate dysarthria and 10 cases of severe dysarthria. In ataxic dysarthria, pitch break was found in 6 out of 10 subjects. It was found that there is negative predictive value 93.33%, and positive predictive value, 77.14% in spastic dysarthria and negative predictive value, 83.33% and positive predictive value, 90.90% in ataxic, whereas negative predictive value, 85.71% and positive predictive value, 95.34% in hypo kinetic dysarthria. Conclusions: Different types of dysarthria when analyzed with software tool after extracting pitch and formants showed specific patterns. These patterns correlated with the clinical diagnosis. And Pattern recognition of different dysarthria will help to identify the types of dysarthria in scientific way and prevent inter-subject variability.